Interaction between the severity of the infection by the nematode Anguillicola crassus and the tolerance to hypoxia in the European eel Anguilla anguilla - François Lefebvre; Pascal Contournet; Alain Crivelli (Acta Parasitologica, 2007)
An experiment was conducted to test the effect of the infection by the swimbladder nematode Anguillicola crassus on the survival of the European eel Anguilla anguilla when exposed to hypoxic conditions. Forty-four wild caught and naturally infected eels were placed in an aquarium filled with water from the fishing site (Vaccarès Lagoon, French Mediterranean coast). In this confined environment (271), under decreasing oxygen resources, the first eel death occurred after 45 h (O2 = 0.98 mg l−1) and the last one after 96 h (O2 = 0.48 mg l−1). After dissection and parasite examination, analyses revealed significant negative correlations between the time to death and various parameters of parasite pressure (e.g., number of lumen worms, parasite mass, health state of the infected organ). It was shown that the severity of damage to the swimbladder rather than the count of living parasites was the major contributing factor in explaining the variation in time to death. These semi-experimental data demonstrating an increased eel mortality rate under severe oxygen stress are discussed for their relevance under field conditions, especially during hot summer months.